Bergamot Reduces Plasma Lipids, Atherogenic Small Dense LDL, and Subclinical Atherosclerosis in Subjects with Moderate Hypercholesterolemia: A 6 Months Prospective Study - Toth, Peter P.; Patti, Angelo M.; Nikolic, Dragana; Giglio, Rosaria V.; Castellino, Giuseppa; Biancucci, Teresa; Geraci, Fabiana; David, Sabrina; Montalto, Giuseppe; Rizvi, Ali; Rizzo, Manfredi (Frontiers in Pharmacology, 2016)
Background: Some patients experience statin-induced side effects or prefer nutraceutical approaches for the treatment of dyslipidemia. This has led to a search for alternative therapeutic approaches for dyslipidemia management. In recent studies Citrus bergamia (known as Bergamot) juice was able to reduce serum levels of lipids. Such benefit may be attributed to high amounts of flavonoids contained in Bergamot fruit juice (neoeriocitrin, neohesperidin, naringin). The aim of the present study was to fully investigate the effects of a Bergamot extract on cardio-metabolic parameters, including plasma lipids, atherogenic lipoproteins and subclinical atherosclerosis. Methods: Eighty subjects (42 men and 38 women, mean age: 55±13 years) with moderate hypercholesterolemia (e.g., with plasma LDL-cholesterol concentrations between 160 and 190 mg/dl [between 4.1 and 4.9 mmol/l]) were included. A Bergamot-derived extract (Bergavit®) was given at a fixed dose daily (150 mg of flavonoids, with 16% of neoeriocitrin, 47% of neohesperidin and 37% of naringin) for 6 months. Lipoprotein subfractions were assessed by gel electrophoresis. With this methodology low density lipoprotein (LDL) subclasses are distributed as seven bands (LDL-1 and -2 as large LDL, and LDL-3 to -7 as atherogenic small, dense LDL). Subclinical atherosclerosis was assessed by carotid intima-media thickness (cIMT) using B-mode ultrasound. Results: After 6 months, Bergavit® reduced total cholesterol (from 6.6±0.4 to 5.8±1.1 mmol/l, p<0.0001), triglycerides (from 1.8±0.6 to 1.5±0.9 mmol/l, p=0.0020), and LDL-cholesterol (from 4.6±0.2 to 3.7±1.0 mmol/l, p<0.0001), while HDL- cholesterol increased (from 1.3±0.2 to 1.4±0.4 mmol/l, p<0.0007). In addition, a significant increase in LDL-1 (from 41.2±0.2 to 49.6±0.2 %, p<0.0001) was accompanied by decreased small, dense LDL-3, -4 and 5 particles (from 14.5±0.1% to 9.0±0.1% p<0.0001; 3.2±0.1% to 1.5±0.1% p=0.0053; 0.3±0.0% to 0.1±0.0 % p=0.0133, respectively). cIMT also decreased from 1.2±0.4 to 0.9±0.1 mm (p<0.0001). Conclusion: This is the first study investigating the effects of Bergamot flavonoids supplementation on cardio-metabolic risk in dyslipidemic subjects. Bergavit® (Bergamot juice extract) supplementation significantly reduced plasma lipids and improved the lipoprotein profile. cIMT was also reduced significantly over a relatively short time frame of 6 months.